Strengthening CrFeCoNiMn0.75Cu0.25 high entropy alloy via laser shock peening. (July 2022) - Fu, Wujing; Huang, Yongjiang; Sun, Jianfei; Ngan, Alfonso H.W.
Highlights: Laser shock peening is an effective way to introduce gradient structures that improve the mechanical properties of high entropy alloy (HEA). A hardened layer of several hundred micrometers is produced on the surface of HEA via laser shock peening. Twin boundaries, dense dislocations, and grain refinement in the laser affected layer result in enhanced yield strength of HEA. Excellent plasticity during loading of the laser-treated HEA is mainly accommodated by dislocations in the laser unaffected core region. Abstract: For most metallic materials, surface hardening via modifying the near-surface microstructure is an effective method for improving mechanical properties. Among these processes, laser shock peening (LSP), which is versatile and nondestructive to the fabricated product shape, has received much attention. The present work has shown that the mechanical properties of CrFeCoNiMn0.75 Cu0.25 high entropy alloy (HEA) have a significant improvement after LSP treatment. Yield strength more than two times of as-cast alloys is achieved in HEA samples treated by LSP for 4 cycles, due to the introduction of a gradient microstructure comprising subgrains, dense dislocations and nano-twins near the treated surface. The combination of dislocation hardening and mechanical twinning improves the strain hardening ability for the LSP-treated HEA, leading to excellent plasticity during tensile loading. Grain refinement also takes place via a faulting process of dislocation dissociation on nearly every 111 plane. Then, TEM observations and finite simulation of the LSP processed HEA samples after different levels of accumulated strain demonstrate that further tensile deformation is mainly accommodated by dislocations in the core region of the sample unaffected by the LSP, while the top LSP-affected layer accommodates little further plasticity as it is sufficiently hardened by the LSP. The present results indicate the possibility to develop gradient-structured HEAs with excellent mechanical properties using laser shock peening.